Pain control in thoracic oncology. Issue 3 (10th September 2017) - Peeters-Asdourian, Christine; Massard, Gilbert; Rana, Paragi H.; Van Houtte, Paul; White, Andrew P.; Grigoriu, Bogdan; Lossignol, Dominique; Almalki, Mohammed; Alexiou, Jean; Engelholm, Jean-Luc; Sculier, Jean-Paul
This review of pain management in lung cancer is based on the presentation of four cases of thoracic oncology patients with pain at various stages of their disease. The approach will be multidisciplinary, involving a thoracic oncologist, radiologist, thoracic and orthopaedic spine surgeon, radiation therapist, pain medicine specialist, and palliative care specialist. This multispecialty approach to the management of different painful presentations in thoracic oncology will demonstrate the complexity of each case and the improved patient outcomes which result from the involvement of different disciplines working in concert. In the USA, Europe and other countries, palliative care specialists often become rapidly involved in the management of these patients, coordinating social care and providing psychological support. Thoracic and orthopaedic spine subspecialists provide surgical methods to control tumour invasion, and improve quality of life and preservation of function in settings of even diffuse metastatic disease. Similarly, thoracic oncology and radiation therapists utilise both therapeutic and palliative chemotherapeutic and radiation therapy regimens to prolong and improve quality of life. The pain medicine specialist can, in addition to medication management, offer a variety of interventional approaches including unique drug delivery systems such as epidural analgesia, regional anaesthesia techniques, and intrathecal pumps, as well as neuromodulation techniques and neurolytic or neuroablative procedures. In the USA, these specialists complete an additional fellowship year in pain medicine following the completion of an anaesthesiology, physical medicine and rehabilitation, neurology or psychiatry residency. These programmes are accredited by the Accreditation Council for Graduate Medical Education, or ACGME (www.acgme.org ). The availability of opioids and analgesic adjuvant medications is of great benefit in the management of cancer pain http://ow.ly/CgIF30e2UkY